Do Youth Employment Programs Improve Labor Market Outcomes? A Systematic Review - Jochen Kluve; Susanna Puerto; David Robalino; José Manuel Romero; Friederike Rother; Jonathan Stöterau; Felix Weidenkaff; Marc Witte (RWI - Leibniz-Institut für Wirtschaftsforschung, 2016)
This study reviews the evidence on the labor market impact of youth employment programs. We analyze the effectiveness of interventions, and factors that influence program performance including country context, target beneficiaries, program design, implementation, and evaluation type. We identify 113 impact evaluations covering a wide range of methodologies, interventions, and countries. The meta-analysis synthesizes the evidence based on 2,259 effect sizes (Standardized Mean Differences) and the statistical significance of 3,105 impact estimates (Positive and Statistically Significant). Just more than one-third of youth employment program evaluations worldwide show a significant positive impact on labor market outcomes - either employment rates or earnings. In general, programs have been more successful in middle- and low-income countries; this may be because programs' investments are especially helpful for the most vulnerable population groups that they target. We conjecture that recent programs might have benefited from innovations in design and implementation. In middle-low income countries, skills training and entrepreneurship programs have had a higher impact. In high-income countries, the role of intervention type is less decisive - much depends on context and how services are chosen and delivered, a result that holds across country types. We find evidence that programs integrating multiple interventions more likely succeed because they respond better to different needs of beneficiaries. Results also point to the importance of profiling and follow-up systems in determining program performance, as well as to incentive systems for services providers.
Keywords: J21; J48; E24; 330; youth employment; active labor market policy; systematic review; meta-analysis